Effectiveness of pain neuroscience education, motivational interviewing and cognition targeted exercise therapy in patients with chronic neck pain: protocol for a multicentre randomised controlled trial (the COGMO-AP study) - Jo Nijs; Anneleen Malfliet; David Morales Tejera; María Adoración Prieto Aldana; María Isabel Gallardo Vidal; Elena Polentinos Castro; María Teresa Linares Fernández; J Fernández-Carnero (BMJ Open, 2025)
Introduction In primary care, the prevalence of neck pain has increased substantially. Evidence regarding treatment of chronic neck pain (CNP) is scarce, and its effectiveness is not entirely proven in different stages of chronicity, nor for different types of cervical disorders. The goal of this study is to evaluate the effectiveness of a complex intervention (COGMO intervention) compared with usual practice in primary care physiotherapy to improve neck pain intensity, severity and disability in patients with CNP.Methods and analysis Design: a pragmatic cluster-randomised clinical trial design with a 12-month follow-up. Setting: primary care. Participants: physiotherapists as randomisation unit, and patients as analysis unit. Inclusion criteria: individuals aged 18 to 65 years suffering from moderate to severe CNP. Sample size expected: 142 patients. Recruitment: patients referred from primary care physicians to physiotherapy. Intervention: pain neuroscience education (PNE), motivational interviewing (MI) and cognition targeted exercise therapy (CTE) compared with the standard treatment in primary care. Outcomes: the main variable is reduction in pain intensity; secondary variables include pain severity, conditioned pain modulation, temporal summation, neck disability, fear/avoidance behaviour, kinesiophobia, catastrophising, therapeutic alliance and quality of life. Sociodemographic information and adherence to the intervention will be recorded. Data collection: baseline, and follow-up at 3, 6 and 12 months. Analysis: it will follow intention-to-treat principles, and difference in percentage of subjects achieving success on the primary endpoint at 12 months. A model with multilevel analysis will be adjusted through logistic regression (being the dependent variable pain intensity, and the independent, the intervention).Ethics and dissemination Ethical approval has been awarded by the Regional Ethics Committee of Madrid (code: COGMO-AP) and the primary health care central commission of research (code: 20210011). The results of the study will be disseminated through international peer-reviewed journals, international conferences, press and social media.Trial registration number NCT05785455.